Readings in social theory : (McGraw-Hill, 2004)
This highly regarded anthology of primary readings in sociological theory covers the major theorist and schools from classic to contemporary to modernist and postmodernist in a chronological organization. While designed to be a supplementary reader, its comprehensive coverage and excellent introductions make this book appealing as a main text for professors who want to encourage their students to read and interpret original sources without a traditional main text